Rekonstruksi Penanganan Perkara Pidana melalui Restorative Justice Berbasis Kepastian Hukum di Polda Gorontalo - Wawan Thaib; Roy Marthen Moonti; Ibrahim Ahmad (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the application of restorative justice in handling criminal cases at the Gorontalo Regional Police and formulate a reconstruction model based on legal certainty and protection of victims' rights. The study uses empirical legal methods with a juridical-sociological, legislative, and conceptual approach. Primary data were obtained through interviews with investigators, victims, perpetrators, legal advisors, and community leaders, while secondary data were sourced from laws and regulations, books, journals, decisions, and case documents. Data were analyzed qualitatively through reduction, presentation, and drawing conclusions. The results of the study indicate that the application of restorative justice still faces differences in interpretation of material and formal requirements, lack of uniformity in case eligibility indicators, weak inter-institutional coordination, and suboptimal guarantees of voluntariness and victim recovery. Peace is often still understood administratively through a written agreement, without ensuring the implementation of restitution, rehabilitation, security protection, and prevention of re-victimization. Therefore, reconstruction is needed in the form of technical guidelines, case assessment matrices, victim loss and vulnerability assessments, tiered case titles, professional assistance, an integrated database, and a monitoring mechanism for the implementation of the agreement. This model is expected to achieve consistent, transparent, accountable, and substantively just case handling, while also providing legal certainty for victims, perpetrators, law enforcement officials, and the community. This reconstruction also places the fulfillment of victims' rights as the primary measure of successful criminal case resolution through a sustainable restorative approach.